2015
DOI: 10.1002/ece3.1648
|View full text |Cite
|
Sign up to set email alerts
|

Mind the gap: treefalls as drivers of parental trade‐offs

Abstract: Tree‐fall gaps are small‐scale disturbances whose formation, colonization, and role in forest dynamics are well documented, but whose effects on animal ecology are still greatly overlooked, except for studies comparing species richness of gaps 6+ months old to that in the closed canopy. Other factors associated with the invasion of fresh tree‐fall gaps such as animal breeding adaptations have been largely neglected. I studied the immediate (within hours and days) arrival of the poison frog Dendrobates tinctori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 74 publications
2
36
0
Order By: Relevance
“…Finally, other indirect cues, such as pool-associated microhabitat (e.g., as in salamanders ( Jenkins, McGarigal & Timm, 2006 )) or calls of heterospecifics (e.g., as in newts ( Diego-Rasilla & Luengo, 2007 )), might be used by tadpole-transporting frogs to discover breeding sites. For example, transporting males of the poison frog Dendrobates tinctorius were found to gather at sites of fresh treefalls, which often provide new deposition sites ( Rojas, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, other indirect cues, such as pool-associated microhabitat (e.g., as in salamanders ( Jenkins, McGarigal & Timm, 2006 )) or calls of heterospecifics (e.g., as in newts ( Diego-Rasilla & Luengo, 2007 )), might be used by tadpole-transporting frogs to discover breeding sites. For example, transporting males of the poison frog Dendrobates tinctorius were found to gather at sites of fresh treefalls, which often provide new deposition sites ( Rojas, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…), even conspecifics ( Fig. 7A; Rojas , 2015. Tadpole 256 mouthparts are well suited for their carnivorous diet, with hardened serrated jaw sheath (Silverstone 1975; 257 Some males carrying more than one tadpole were seen depositing one of them in a pool and leaving with 266 the second tadpole still attached to their back, whereas other males were seen depositing their two 267 tadpoles in the same pool, at the same time.…”
Section: Larval Development and Patterns Of Tadpole Transport 251mentioning
confidence: 99%
“…These structures are 307 used as oviposition sites (this study), and are also the types of structures that accumulate rainwater, Males' association with structured habitats may also be the key reason why they are more likely to be 317 found in tree-fall gaps long after their formation. A recent study reported higher tadpole deposition rates 318 in pools at recent tree-fall gaps in comparison to pools in the closed forest (Rojas 2015), suggesting that 319 the availability of new places for tadpole deposition is one of the drivers of tree-fall gap invasion in this 320 species. However, the immediate arrival in tree-fall gaps is not exclusive of males.…”
mentioning
confidence: 99%
“…Finally, other indirect cues, such as pool-associated microhabitat (e.g., as in salamanders (Jenkins, McGarigal & Timm, 2006)) or calls of heterospecifics (e.g., as in newts (Diego-Rasilla & Luengo, 2007)), might be used by tadpoletransporting frogs to discover breeding sites. For example, transporting males of the poison frog Dendrobates tinctorius were found to gather at sites of fresh treefalls, which often provide new deposition sites (Rojas, 2015).…”
Section: Pool Visitsmentioning
confidence: 99%